Perancangan Sistem Parkir Pada Gedung Menara Palma Jakarta - Anggi Oktaviani; Dahlia Sarkawi; Agus Priadi (Sekolah Tinggi Teknik - PLN, 2019)
Parking pool or parking area is a place provided for parking of motorized vehicles outside of the road whih is provided by individual or institution, including motorized vehicle storage and motorized vehicle garage. In managing the parking pool, the parking owner must have a system to facilitate the processing of the parking area. The existing parking system at Palma tower building Jakarta is still manual, that is by entering the vehicle number into the computer by operator, then printing. The parking ticket provided is only a form of paper containing the vehicle number and vehicle entry time. Payment transactions method made by parking operators are currently not efficient, because the level of officer error when calculate parking fees and change money is high. Deal with these various problems, an idea arises to create a subscription parking system by using an automated parking system. This automated parking system is named with an RFID system (Radio Frequency Identification). The design of this automatic parking system is the best solution to solve the problems that are already running. This computerized system is better than a manual system because this system can run more effectively and efficiently and it is more conducive than the previous system.